(untitled) (New York, 1979)
This is the first volume in a new series which sets out to debate and to disseminate progress in research and applications in a broad field entitled spatial analysis, industry, and the industrial environment.
Keywords: Industrial location,Manufactures,Khu công nghiệp,Nhà máy sản xuất